Application of the Technique For Order Preference By Similarity To Ideal Solution Method in Determining Contract Employees to Become Permanent Employees - Resmi, Mochzen Gito; Defriani, Meriska (Politeknik Ganesha Medan, 2021)
Refratech Mandala Perkasa (RMP) is a refractory cement manufacturing company. The company also operates in the manufacture of refractory cement made for repair of hot coatings, boilers, rotary kilns, incinerators, ovens and chemicals for steel metals, as well as ferrous & non ferrous foundries. In this company there are contract employees and permanent employees, contract employees are employees or workers whose working period is limited by a certain time according to the agreement within the company. While permanent employees are workers whose working period is approximately until they receive certain benefits according to the work agreement. This research was conducted to assist companies in decision support using the Topsis method in determining the appointment of contract employees to permanent employees based on predetermined criteria, namely Knowledge and Skills at work, Quantity and Quality of Work, Job Responsibilities, Initiatives in Work, and Compliance. on rules or discipline. The results of this study indicate that the determination of the ranking of prospective permanent employees can be obtained from the calculation results of the TOPSIS method, where the results of prospective employees are based on predetermined administrative criteria. Prospective permanent employees who have the highest rank have the right to be selected first. The accuracy of the implementation of the TOPSIS method on the system plays a major role in the effectiveness and efficiency of the company's services to consumers compared to before the system was implemented. With the implementation of this DSS system, it can help companies to make it easier to make decisions to survey prospective permanent employees and optimize employee performance.